The hydrogen plasma injector with the metal-hydride hollow cathode - Tseluyko, A.F.; Borisko, V.N.; Zinov'ev, D.V. (Вопросы атомной науки и техники, 2005)
The intensive pulse source for synthesized electron-ion beams on the basis of the Penning discharge with the metal hydride hollow cathode was investigated. The main feature of this device is the application of metal hydride Zr₅₀V₅₀Hx as an electrode material for the hollow cathode. The using of metal hydride hollow cathode allows to provide the pulse working gas feed at low starting pressure р = 10⁻³ Pa. The density of ion current in the source achieved 50… 100 mА/cm² at the energy of ion and electron beams 0,5…1 keV. The comparison of parameters of the charged particles sources in different modes of hollow cathode operations is carried out. Розглядається інтенсивне імпульсне джерело для синтезу електронно-іонних пучків на основі розряду Пенінга з металогідридним порожнистим катодом. Особливістю пристрою є застосування металогідриду Zr₅₀V₅₀Hx в якості матеріалу електрода порожнистого катода. Використання металогідридного порожнистого катода дозволяє забезпечити імпульсну подачу робочого газу при зниженому початковому тиску р = 10⁻⁵ Пa. Щільність струму іонів у джерелі досягає 50…100мА/см² при енергії пучка 0,5...1 кеВ. Проведено порівняння параметрів джерел заряджених часток у різних режимах роботи порожнистого катода. Рассматривается интенсивный импульсный источник для синтеза электронно-ионных пучков на основе разряда Пеннинга с металлогидридным полым катодом. Особенностью устройства является применение металлогидрида Zr₅₀V₅₀Hx в качестве материала электрода полого катода. Использование металлогидридного полого катода позволяет обеспечить импульсную подачу рабочего газа при пониженном начальном давлении р = 10⁻⁵ Пa. Плотность тока ионов в источнике достигает 50…100 мА/cм² при энергии пучка 0,5…1 кэВ. Проведено сравнение параметров источников заряженных частиц в различных режимах работы полого катода.